Ionic transport and influence of electromagnetic field interaction within electric double layer in reservoir sandstone - Sikiru, S. (Elsevier B.V., 2021)
The dielectric properties of reservoir sandstone are controlled by several physical factors such as the size, conductivity, the mineral types, and interaction between the particles are the major constrain in reservoir sandstone. The key issues are the accumulation of ions at the interface between two immiscible liquids (oil/water), solid/liquid interface, and ion separation in terms of polarization mechanisms. This review article discussed in detail the mineralogy overview, the factor responsible for the polarization mechanisms in reservoir sandstone, electric double layer propagation, electrical conduction in reservoir sandstone, the effect of electromagnetic filed within the reservoir sandstone, the cation and anion exchange within the electric double layers for the reduction of interfacial tension in reservoir sandstone, and the complexity of reservoir response with the presence of oil and electrolyte to the electromagnetic field. frequency dependence gives us the clue on the fluid mobility concerning the electromagnetic field. The distribution of cation and anion within the solid/liquid interface are well elucidated due to dielectric relaxation spectral illustration. Â© 2021 Elsevier B.V.